2007
DOI: 10.1002/app.26222
|View full text |Cite
|
Sign up to set email alerts
|

Blends of thermoplastic polyurethane and polypropylene. I. Mechanical and phase behavior

Abstract: Pure thermoplastic polyurethane (TPU), polypropylene (PP), and TPU/PP blends with different weight ratios prepared in a twin-screw extruder were investigated by dynamic mechanical analysis (DMA), the universal tester for mechanical investigation, and by wide-angle X-ray diffraction (WAXD). The addition of PP above 20 wt % to the TPU stepwise changed the ductility and Young's modulus, i.e., apparently a kind of ductile ? brittle transition occurred between TPU/PP 80/20 and TPU/PP 60/40 blends. This fact and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 10 publications
3
41
1
Order By: Relevance
“…The completion of the investigation of the structureproperty relationships of TPU/PP blends through examinations of their thermal and morphological behaviors confirmed some conclusions presented in a previous article 11 and emphasized new conclusions:…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The completion of the investigation of the structureproperty relationships of TPU/PP blends through examinations of their thermal and morphological behaviors confirmed some conclusions presented in a previous article 11 and emphasized new conclusions:…”
Section: Discussionsupporting
confidence: 72%
“…Obviously, the completion of the cocontinuous phase morphology could be expected between the 60/40 TPU/PP and 80/20 TPU/PP blends. These results, as well as the stepwise change in the ductility and Young's modulus, 11 locate the PP matrix to TPU matrix inversion in the concentration region between the 60/40 and 80/20 TPU/PP blends. This is in accordance with some morphological models predicting the occurrence of a cocontinuous (bicontinuous) phase morphology on the basis of the viscosity ratio of the components (the empirical Jordhamo law).…”
Section: Morphological Observationsmentioning
confidence: 68%
See 1 more Smart Citation
“…These results can be attributed to the immiscibility and incompatibility between PP and TPU, which led to an inhomogeneous phase with poor interaction [8]. Qu et al examined the mechanical properties of TPU/PP blends with various contents of TPU (10-90 wt%) and found that a U-shaped mechanical property curve formed when TPU content increased.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that the tensile properties of PP/TPU blends decreased as more TPU was added. Some problems resulted from the larger intrinsic structure of TPU and from interphase interaction and transformations [8], so the proportion of TPU was set at 10 wt%. In the meantime, the pure PP and pure MPP were used as control groups, and the effects of using TPU on the blending morphology, melting behavior, crystalline behavior, and mechanical properties of polymer blends were investigated.…”
Section: Introductionmentioning
confidence: 99%